Prevalence of CXCR4‐tropic viruses in clustered transmission chains at the time of primary HIV‐1 infection. (17th January 2013) - Frange, P.; Meyer, L.; Ghosn, J.; Deveau, C.; Goujard, C.; Duvivier, C.; Tubiana, R.; Rouzioux, C.; Chaix, M.‐L.; ,; Antonelli, G.
Abstract During 2003–2010, 555 strains isolated from sexually‐infected patients at the time of primary HIV‐1 infection (PHI) were characterized. Tree topology revealed that 11.7% of PHIs segregated into transmission clusters. CXCR4‐usage was identified in 27 strains (4.9%) and was significantly associated with subtype B (p 0.003) and low CD4 cell count (p 0.01). In clustered and unique PHIs, the prevalence of CXCR4‐tropic strains was 1.5% and 5.3%, respectively (p 0.35). Our results are in line with the hypothesis of a mucosal bottleneck contributing to the high prevalence of CCR5 variants during PHI.